Oficinas de pensamentos na promoção de experiências filosóficas - Paizan, Silena da Fonseca Pimentel (Universidade Federal de São Carlos, 2020)
This dissertation, entitled “Workshop of thoughts in the promotion of philosophical experience”, presents a way for the philosophy discipline to promote a philosophical experience for the subjects involved in it, as it appears that philosophizing has been rare in the teaching of philosophy, since this has been offered by models and official documents that function as obstacles and distances from the real function of the discipline. Most of the time the teaching of this curricular component was not characterized by the philosophical experience. The objective of this study is to bring philosophizing effectively to teach and learn, valuing the dialogical perspective of the subjects through the sharing of experiences in a collaborative way, from the training of teachers to teaching. The bibliographic research focused on the works of Walter Benjamim, Jorge Larrosa and Walter Kohan. With the analysis of the texts, it was possible to perceive the progressive distance between the subjects, the practice of the discipline and to signal a path for change. Following the theoretical references of Walter Kohan, we seek to facilitate this approach by creating the project entitled Oficina de Pensamentos, where the craft of thinking was prioritized in a collaborative involvement within that learning community and the themes developed in the workshop started from uneasy relationships between students and its truths, in a way we call a philosopher. Therefore, the conclusion reached was that through the Workshop of Thoughts, teaching and learning was reconstructed, through the cooperative sensitivity that started from the experience of those involved, each one within his time and space, promoting the gradual reconstruction of teaching and learning. from learning towards the philosophical experience
Thought workshops to promote philosophical experiences
Keywords: Experiência; Ensinar e aprender; Sujeitos; Filosofia; Filosofar; Experience; Teach and learn; Subject; Philosophy; Philosophize; CIENCIAS HUMANAS::FILOSOFIA::HISTORIA DA FILOSOFIA